2020
DOI: 10.1002/csr.1948
|View full text |Cite
|
Sign up to set email alerts
|

Do environmental, economic and reputational advantages strengthen green practices' impact on environmental performance?

Abstract: In an attempt to curb the hazardous effect of construction activities, there is a heightened debate about whether the perceptions of green practice (GP) advantages will encourage the adoption of GPs and improve environmental performance (EnvP). This article investigates the role of environmental, economic and reputational advantages of GPs and their relationship with EnvP. The data were collected from 148 project managers from the Malaysian construction industry and analysed using partial least square structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Arimura et al (2016) use a five-point scale to assess environmental performance, ranging from a significant reduction to a significant increase in natural resource use and air pollution emissions. Yusof et al (2020) identified energy consumption, pollutant emission and waste reduction and avoiding the use of hazardous materials as common metrics for measuring environmental performance in the construction sector.…”
Section: Conceptual Review Of Environmental Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Arimura et al (2016) use a five-point scale to assess environmental performance, ranging from a significant reduction to a significant increase in natural resource use and air pollution emissions. Yusof et al (2020) identified energy consumption, pollutant emission and waste reduction and avoiding the use of hazardous materials as common metrics for measuring environmental performance in the construction sector.…”
Section: Conceptual Review Of Environmental Performancementioning
confidence: 99%
“…With environmental regulations and certification failing to reduce pollution, questions have arisen in developing countries about whether green practices adopted in the construction sector achieve environmental goals (Yusof et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Dilla et al (2019) indicated that environmental performance is more influential on the evaluation of stakeholders in the enviromental friendly investments with the strong notions on environmental responsibility, and appreciated the important role of environmental responsibility to environmental performance. Yusof (2020) tried to link the adoption of green practices in business with environmental performance, in which green practices refer to the systems of developing structures and employing environmental friendly measures. Environmental friendly practices are recognized as a vital driver in augmenting organizational reputation, so enjoying confidence from investors as well as customers.…”
Section: Influence Of Environmental Responsibility On Environmental Performancementioning
confidence: 99%
“…These green practice can be categorized as internal and external [1]- [4]. Internal green practice refers to the green activities within the firm's area of control [5], while external green practice consists of a series of activities undertaken by the firm to promote and monitor the environmental performance of its suppliers (e.g., green supplier certification, direct investment and joint environmental plans) [3], [6]- [8]. Examples are abundant.…”
Section: ⅰ Introductionmentioning
confidence: 99%